Intersexualidade em caprinos - Pastor López, Francisco Javier; Toniolo Chávari, Andréia Cristina [UNESP]; Schimidt Dibbern, Lucas [UNESP]; Salinas González, Homero; Amorim Ramos, Alcides [UNESP]; Flores Nájera, Manuel De Jesús (My University, 2015)
The objective of this review is to provide basic information about intersexuality, addressing their main characteristics. Based on the literature, the phenomenon of intersex is described as an anatomical alteration where the development of the gonads varies, and in these conditions there productive organs are usually infertile. The hermaphroditic animals can be categorized as true hermaphrodites, when present male and female gonads simultaneously, or pseudo hermaphrodites if they only have the gonads of one sex. Several authors report the intersex by acorn character as the main cause, owing its origin to two genes that regulate gonadal development, this acorn character can cause the absence of horns and infertility. Diagnosis can be made by various methods, from simple anatomical assessment to complex molecular biology techniques, depending on the intensity with which the genes are manifested. However, to avoid problems in goat production is sufficient that one of the parents has horns; this avoids the dominance of the gene of intersexuality.
Intersexuality in goats
Keywords: Diagnosis; Hermaphroditism; Infertility; Sexual characteristics; Small ruminants